2015
DOI: 10.1007/s11628-015-0285-y
|View full text |Cite
|
Sign up to set email alerts
|

Customer participation to co-create value in human transformative services: a study of higher education and health care services

Abstract: Previous studies on customer participation have mainly focused on its outcome benefits. The current study investigates the effect of various participation behaviors on both process and outcome value in human transformative services. Based on the data surveyed from health care and higher education services in Vietnam, the results show that active and relevant participation behaviors are crucial to co-create value. Information sharing, responsible behavior, and voluntary in-role feedback have different roles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 103 publications
1
13
0
1
Order By: Relevance
“…Voluntary behaviour of customers that delivers value to the organisations but are not required to be performed by the customer is known as customer citizenship behaviour (Hau & Thuy 2016). Performed towards the organisation, employees or other customers, these behaviours positively influence the performance and experience of these stakeholders (Bove et al 2009).…”
Section: Customer Citizenship and Helping Behavioursmentioning
confidence: 99%
“…Voluntary behaviour of customers that delivers value to the organisations but are not required to be performed by the customer is known as customer citizenship behaviour (Hau & Thuy 2016). Performed towards the organisation, employees or other customers, these behaviours positively influence the performance and experience of these stakeholders (Bove et al 2009).…”
Section: Customer Citizenship and Helping Behavioursmentioning
confidence: 99%
“…Leading to positive effects on the motivation on employees, establishing that"... understanding how companies can harness the benefits of customer participation is of great importance." (Chen, Chen, & Lin, 2016, p. 493) Customer participation has also been found to increase the perceived process value of a service through new knowledge, developing relationships, and pleasurable experiences (Nguyen Hau & Thuy, 2016). Ethical issues around co-creation and organizational performance have also been explored, where exploitative practices are not necessarily rejected because they are explicitly illegal, but because co-creating stakeholders consider them morally reprehensive (Vial, 2019).…”
Section: Culture and Customer Participation In Digital Transformationmentioning
confidence: 99%
“…In the customer own sphere after meeting with the physician, knowledgeable customers are well aware about the negative effect of non-compliance to medical treatment, and understand what to do, why to do and how to do the participation tasks within his/her own responsibility in the treatment process to ensure the service outcome (Gallan et al 2013;Chan et al 2010). Moreover, it is evidenced that active customer participation is a strong determinant of both process value and outcome value (Hau and Thuy 2016). Thus, it is reasonable to propose the positive relationship between customers' cultural resource and their perception of service value.…”
Section: Cultural Resource and Perceived Valuementioning
confidence: 99%
“…Empirically, some studies in health care have shown that self-efficacy, optimism or positivity emotion have a positive effect on the level of participation and adherence to the service (Gallan et al 2013;Osborn et al 2010;Sarkar et al 2006). In turn, patient's participation and adherence are attributes of value co-creation behaviors which were found to be determinants of perceived value (Yi and Gong 2013;Hau and Thuy 2016). On this basis, the following hypotheses are proposed: H2a There is a positive effect of customer physical resource on customer process value in health care service.…”
Section: Physical Resource and Perceived Valuementioning
confidence: 99%